2000
DOI: 10.2165/00063030-200014010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Management of Liver Transplant Rejection in Children

Abstract: The current management of hepatic allograft rejection after liver transplantation in children requires effective baseline immunosuppression to prevent rejection and rapid diagnosis and treatment to manage acute rejection episodes. The subsequent impact on chronic rejection is dependent on the combination of adequate prevention and the treatment of acute rejection. Tacrolimus is a macrolide lactone that inhibits the signal transduction of interleukin-2 (IL-2) via calcineurin inhibition. Introduced in 1989, tacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…On the other hand, Mazariegos et al reported fi nding that muromonab-CD3 was effective against ACR or early CR, especially in recipients initially treated with tacrolimus. 15 In our patient, the CD3 + T-cell counts decreased after muromonab-CD3 administration, descending further with subsequent doses of muromonab-CD3 and recovering to within the normal range after discontinuation. Several side effects can occur during the abatement and restitution of CD3 + T cells with muromonab-CD3 administration.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…On the other hand, Mazariegos et al reported fi nding that muromonab-CD3 was effective against ACR or early CR, especially in recipients initially treated with tacrolimus. 15 In our patient, the CD3 + T-cell counts decreased after muromonab-CD3 administration, descending further with subsequent doses of muromonab-CD3 and recovering to within the normal range after discontinuation. Several side effects can occur during the abatement and restitution of CD3 + T cells with muromonab-CD3 administration.…”
Section: Discussionsupporting
confidence: 47%
“…14 Early CR, including ACR, in recipients treated initially with tacrolimus responded well to muromonab-CD3. 15 We think that the induction phase of muromonab-CD3 was during ACR in our patient, which did not seem reasonable; however, this case fulfi lled some requirements for the induction of muromonab-CD3 for refractory ACR as specifi ed in previous reports. We decided on induction for this patient after careful consideration based on the severe lymphocyte infi ltration, comparatively early period after LT (PODs 24-31), coagulopathy, and proteinlosing ascites.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…34,35 Since the late 1980s, OKT3 administration in liver transplantation was largely confined to steroid-resistant acute rejections, with a long-term graft survival rate of approximately 50%. [36][37][38] Its usage was specifically contraindicated in hepatitis C virus (HCV) infected patients because OKT3 treatment was associated with worse outcomes. [39][40][41] Finally, in comparative OKT3 studies in lung transplant patients, RATG produced fewer side-effects, a lower incidence of BOS, and superior 5-year survival outcomes (52% RATG versus 34% OKT3).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…IV administration of tacrolimus (0.05 to 0.1 mg/kg/day) may be required when oral absorption is poor or unpredictable, although this is rare. [20,37] In refractory acute rejection a tapered regimen of methylprednisolone is also used (see table II). Monoclonal antibody therapy is used in conjunction with tacrolimus conversion only if there is biopsy evidence of residual cellular rejection after a cycle of methylprednisolone therapy.…”
Section: Patients With Acute or Chronic Rejectionmentioning
confidence: 99%